Reverse and forward engineering multicellular structures with optogenetics. (December 2020) - Mumford, Thomas R.; Roth, Lee; Bugaj, Lukasz J.
Abstract: Understanding how cells self-organize into functional higher-order structures is of great interest, both towards deciphering animal development and for our ability to predictably build custom tissues to meet research and therapeutic needs. The proper organization of cells across length scales results from interconnected and dynamic networks of molecules and cells. Optogenetic probes provide dynamic and tunable control over molecular events within cells, and thus represent a powerful approach to both dissect and control collective cell behaviors. Here, we emphasize the breadth of the optogenetic tool kit and discuss how these methods have already been used to reverse engineer the design rules of developing organisms. We also offer our perspective on the rich potential for optogenetics to power forward-engineering of tissue assembly towards the generation of bespoke tissues with user-defined properties. Graphical abstract: Image 1 Highlights: Optogenetics enables tunable light control over the molecular building blocks that regulate cell behaviors. Optogenetics allows researchers to dissect the developmental programs that shape and organize growing tissue. Light control of biological programs can aid the construction of user-designed tissue with custom properties and functions.